2015
DOI: 10.1136/annrheumdis-2015-eular.6384
|View full text |Cite
|
Sign up to set email alerts
|

AB0331 Incidence and Predictors of Cardiovascular Events Over a Period of 5 Years in a Cohort of Women with Rheumatoid Arthritis: Table 1.

Abstract: BackgroundAn excess in cardiovascular (CV) morbidity and mortality has been recognized in Rheumatoid Arthritis (RA) patients when compared to the general population.ObjectivesOur aim was to estimate the incidence of CV events and the contribution of traditional CVD risk factors and RA-related parameters to future events.MethodsIncident fatal and non-fatal CV events (hospitalizations due to unstable angina, myocardial infarction, coronary artery revascularization procedures, stroke, or CV death) were assessed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Higher levels were found to increased cardiovascular mortality rate and predicted future events [34]. Furthermore, Castro et al stated that ESR and ICAM seem to be independent predictor of cardiovascular events [24]. We found significantly elevated levels of ICAM in RA patients, but we found no correlation between ICAM and asympthomatic atherosclerosis in RA patients.…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…Higher levels were found to increased cardiovascular mortality rate and predicted future events [34]. Furthermore, Castro et al stated that ESR and ICAM seem to be independent predictor of cardiovascular events [24]. We found significantly elevated levels of ICAM in RA patients, but we found no correlation between ICAM and asympthomatic atherosclerosis in RA patients.…”
Section: Discussioncontrasting
confidence: 62%
“…The clinical relevance of our findings is even more important if we consider that the previously published studies showed that the risk of acute myocardial infarction increases for 43% for every 0.163 mm increase in cIMT and that the prevalence of carotid plaque is even a more reliable predictor of cardiovascular events [1,13,[24][25][26][27]. Recent study of Corrales et al [28] also showed that the presence of carotid plaques predicted the development of CV events and death in RA patients.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“… 23 Similarly, a Portuguese cohort of RA women reported a rate of 7 per 1000 person-years. 24 In England, the incidence rate was 35.33 per 1000 person-years, using a broader definition of CVD that included twelve different presentations. 25 Note that all rates were standardized to per 1000 person-years for comparison.…”
Section: Discussionmentioning
confidence: 99%